Fixations Gate Species-Specific Responses to Free Viewing of Faces in the Human and Macaque Amygdala - Minxha, Juri; Mosher, Clayton; Morrow, Jeremiah K.; Mamelak, Adam N.; Adolphs, Ralph; Gothard, Katalin M.; Rutishauser, Ueli (Cell reports (Cambridge), 2017)
Neurons in the primate amygdala respond prominently to faces. This implicates the amygdala in the processing of socially significant stimuli, yet its contribution to social perception remains poorly understood. We evaluated the representation of faces in the primate amygdala during naturalistic conditions by recording from both human and macaque amygdala neurons during free viewing of identical arrays of images with concurrent eye tracking. Neurons responded to faces only when they were fixated, suggesting that neuronal activity was gated by visual attention. Further experiments in humans utilizing covert attention confirmed this hypothesis. In both species, the majority of face-selective neurons preferred faces of conspecifics, a bias also seen behaviorally in first fixation preferences. Response latencies, relative to fixation onset, were shortest for conspecific-selective neurons and were ∼100 ms shorter in monkeys compared to humans. This argues that attention to faces gates amygdala responses, which in turn prioritize species-typical information for further processing. [Display omitted] •Investigated the role of the human and macaque amygdala in face processing•Response of face-selective neurons was gated by fixations during free viewing•Response latencies were shortest when fixating on a face of the subject’s own species•Covert attention gated human amygdala responses to faces The role of the amygdala in social perception remains unknown. Minxha et al. reveal that the response of face-selective amygdala neurons in macaques and humans is gated by fixations and the species of the fixated face. This shows that primate amygdala responses to social stimuli are gated by attention.